EFISIENSI TEKNIS PENDIDIKAN DI KOTA SURAKARTA: APLIKASI DATA ENVELOPMENT ANALYSIS (DEA) - Isa, Muzakar (Benefit: Jurnal Manajemen dan Bisnis, 2009)
The purpose of this study to analyze the factors that affect achievement in state andÂ private high school in Surakarta in the academic year 2005/2006, and measure the level ofÂ technical efficiency of high school in Surakarta in 2006. The analytical tool used are multipleÂ linear regression and DEA. The analytical tool used ar multiple linear regression and DEA.Â The results showed that 70.73 percent of high school in Surakarta is efficient, and 29.27Â percent, inefficient. High schools in Surakarta on average are efficient. High school achievementÂ in Surakarta in 2006Â was influencedbyÂ student-teacherÂ ratio,Â the ratio of studentsâadministrativeÂ staff, the ratioÂ of teacher experiencefor 15 years,Â theÂ ratioÂ of graduateÂ teacher education, and the average value of new students NEM (score of pure national exam). English is the dominant output variables that cause inefficiencies high school in Surakarta.